Evaluation and management of intrahepatic and extrahepatic cholangiocarcinoma. Issue 9 (22nd January 2016) - Esnaola, Nestor F.; Meyer, Joshua E.; Karachristos, Andreas; Maranki, Jennifer L.; Camp, E. Ramsay; Denlinger, Crystal S.
Abstract : Cholangiocarcinomas are rare biliary tract tumors that are often challenging to diagnose and treat. Cholangiocarcinomas are generally categorized as intrahepatic or extrahepatic depending on their anatomic location. The majority of patients with cholangiocarcinoma do not have any of the known or suspected risk factors and present with advanced disease. The optimal evaluation and management of patients with cholangiocarcinoma requires thoughtful integration of clinical information, imaging studies, cytology and/or histology, as well as prompt multidisciplinary evaluation. The current review focuses on recent advances in the diagnosis and treatment of patients with cholangiocarcinoma and, in particular, on the role of endoscopy, surgery, transplantation, radiotherapy, systemic therapy, and liver‐directed therapies in the curative or palliative treatment of these individuals. Cancer 2016;122:1349–1369 . © 2016 American Cancer Society . Abstract : Cholangiocarcinomas are rare biliary tract tumors that are often challenging to diagnose and treat. This review focuses on recent advances in endoscopy, surgery, transplantation, radiotherapy, systemic therapy, and liver‐directed therapies in the curative or palliative treatment of patients with these tumors.